Aplikasi Bantu Pembelajaran Huruf dan Angka Braille - Priyanto, Dadang; Nur, Muhammad (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
Ministry of Research, Technology and Higher Education of the Republic of Indonesia (henceforth Kemenristek Dikti RI) through the Science and Technology for Community program (henceforth IbM) as one of the community services schemes, has been implemented in SLBN (Sekolah Luar Biasa Negeri) Pembina West Nusa Tenggara Province (NTB) and SLBA (Tuna Netra) Selagalas Mataram. The program having aims are as follows: (1) Implement the application of Letter and Number recognition for the visionless child; (2) Facilitate students for the letter and number Braille recognition in SLB; (3) Support the teacher/mentor in teaching activity during the students learning, since the smart system application is for independent learning; (4) Assist the government program in education sector for the basic needs of child with regardless status. The implementation method in the application was the system Development Life Cycle (SDLC) and the method in developing application system was the Mallon’s Model. The application has been implemented through the short course of trial training for students and teacher/mentor in both institutions SLBN Pembina NTB Province and SLBA Tuna Netra Selagalas Mataram